Methodology For Determining The Quality Of Hadith Nashiruddin Al-Albani (Analysis Of The Book Silsilat Al-Ahadits Al-Shahihah And Silsilat Al-Ahadits Al-Dha'ifah) - Fadhil, Azhar; Kasman, Kasman; Pujiono, Pujiono (International Journal of Educational Research & Social Sciences, 2023)
The authenticity of the hadith is not the same as the authenticity of the al-Qur’an, where the al-Qur’an itself has received justification directly from Allah Ta'ala. In contrast to the hadith which requires quite a lot of research to see how the quality of the hadith is from both the sanad and the matan. There have been many hadith scientists who have tried to organize various methods of maintaining the existence of the hadith itself. Among the many scientists, al-Albani is one of them who has devoted himself to studying the applicable concepts in the study of hadith science. As a person who loves hadiths, al-Albani does not just accept the hadiths he reads even though these hadiths have been researched beforehand. It was this caution that made al-Albani develop his own method, although it cannot be denied that the method used by al-Albani was not much different from the methods of previous scholars.